Thelypteridaceae (Polypodiopsida) in Pakistan - Muhammad Irfan; Susan Fawcett (Journal of Animal and Plant Sciences, 2024)
The present treatment of Thelypteridaceae (Polypodiopsida) in Pakistan is based on the study of fern specimens in 15 herbaria in Asia, Europe and USA. A total of six genera and eight species were identified; a key, detailed description of species, general distribution in Pakistan and worldwide, ecology, and a list of specimens examined from Pakistan are provided.
Keywords: Key to genera; Pteridophyte species; Taxonomy; Thelypteridaceae; Pakistan